Application of hopcalite catalyst for controlling carbon monoxide emission at cold-start emission conditions - Dey S.; Dhal G.C.; Mohan D.; Prasad R. (My University, 2025)
Carbon monoxide (CO) is a poisonous gas particularly to all leaving being present in the atmosphere. An estimate has shown that the vehicular exhaust contributes the largest source of CO pollution in developed countries. Due to the exponentially increasing number of automobile vehicles on roads, CO concentrations have reached an alarming level in urban areas. To control this vehicular exhaust pollution, the end-of-pipe-technology using catalytic converters is recommended. The catalysts operating efficiently in a catalytic converter are a challenging class of materials for applications in cold start of engines to maintain indoor air quality. In the cold start period, the catalytic converter was entirely inactive, because the catalytic converter had not been warmed up. The cold start phase is also depending upon the characteristics of vehicles and property of catalysts. The increasing cost of noble metals with the increasing number of vehicles motivates the investigation of material concepts to reduce the precious metal content in automotive catalysts or to find a substitute for noble metals. Hopcalite (CuMnOx) catalyst could work very well at the low temperature; thus, it can overcome the problem of cold-start emissions if used in a catalytic converter. Further, low cost, easy availability and advanced synthesis methods with stabilizer, promoter, etc., advocates for the use of hopcalite as an auto exhaust purification catalyst. Although there are numerous research articles present on this topic until now, no review has been presented for demanding this issue. So there is a space in this area, and it has been made an attempt to seal this hole and progress the future scope for hopcalite catalyst for purification of exhaust gases by this review. © 2019 The Authors